The influence of leadership style and work motivation on the teachers performance of senior high school 1 of west semendawai - Satriana Tantiwi; Bukman Lian; Alhadi Yan Putra (Journal of Educational and Learning Studies, 2021)
The purpose of this study is to determine the effect of leadership style and work motivation on the performance of teachers at senior high school 1 of Semendawai Barat. This research is conducted in the world of education which focuses on schools, namely senior high school 1 of Semendawai Barat from June to September 2020.Data collection techniques used in this study among are questionnaire, observation and documentation. Respondents in this study were 45 teachers. The data analysis method used quantitative analysis, using the SPSS 21 application. The analysis carried out was the correlation analysis of the t test and the F test. The results of the data analysis from the questionnaire showed that the results of the t-value test were 11,257 with a sig level of 0,000, so the hypothesis was concluded that there was an influence of leadership style. on the performance of teachers at senior high school 1 of Semendawai Barat is accepted. The results of the analysis of R Square 0.835 indicate that about 83.5% of the effect on variable Y can be explained by variations in variable X1.The result of the t-value test is 11,960 with a sig level of 0,000, so the hypothesis that there is an influence of work motivation on the performance of teachers in senior high school 1 of Semendawai Barat is accepted. R Square 0.815 shows that about 81.5% of the variation that occurs in variable Y can be explained by variations in variable X2. The results of the multiple regression test of the influence of the variable leadership style (X1) and the work motivation variable (X2) on performance (Y) can be concluded that based on the results of the ANOVA test whose F value is 77,362 sig is 0,000 <0.005, then hypothesis 3 is accepted, and variables X1 and X2 have an effect. significant towards Y variable and the amount of influence is 86.3% while the remaining 13.7% is influenced by other variables outside of leadership style and work motivation. The multiple regression equation for the variables X1 and X2 against Y is = 4.399 + 0.343X1 + 0.526X2 + e.